International Taxation - Islam, Adnan (Aicpa Ser., 2020)
Whether your organization is contemplating a global move or is already involved in international business, you need to know about the activities that create multi-jurisdictional tax exposure and the required tax reporting for each relevant jurisdiction. Information is provided for Tax Reform and the impact of the Tax Cuts and Jobs Act of 2017, this guide covers international tax terminology and regulations that apply to a U.S. entity involved in global operations, or for a foreign entity doing business in the United States. Key topics include: Export income Receipts in foreign currency Allocation and apportionment of deductions U.S. foreign tax credit fundamentals and special rules Initiation of foreign operations Foreign branches and affiliated companies Sale of use of tangible property Foreign business operations in the United States Foreign business sales of tangible property in the United States Foreign business provision of services in the United States Exploitation of business assets outside of the United States Use of foreign tangible/intangible property in the United States U.S. withholding taxes on foreign businesses FDII GILTI.